Associação entre o perfil lipídico e fatores de risco cardiovascular em mulheres de Sinop-MT - São José, Joana de Paula (2016)
Cardiovascular diseases (CVD) are the main reason of mortality worldwide. The emergence of these diseases is mainly related with cardiovascular risk factors. Dyslipidemia associated with excess weight due to the fat accumulation in the mesenteric region is an important factor for the increase in these diseases. The aim of this study was to verify the correlation between lipid profile and cardiovascular risk factors in a sample of women from the Sinop-MTcity. We evaluated 132 women aged between 35 and 80 years and were collected blood pressure, anthropometric measurements, blood samples and application of the level of physical activity questionnaire. The anthropometric measurements collected were weight, height, waist circumference (WC) and hip circumference. It was determined serum levels of glucose, triglycerides (TG), total cholesterol (TC), alanine transaminase (ALT), aspartate transaminase (AST), urea, creatinine and C-reactive protein (CRP). The correlation between lipid profile and cardiovascular risk factors were analyzed by analysis of odds ratios and significance level considered was p<0.05. The average age was 57 years. Of the 132 women 38% had hypertension, 30% had hypercholesterolemia (TC ≥200 mg / dl), and of these 27% are not in treatment, 42% of the had high levels of TG (≥150mg / dl) and 37% levels high glucose (≥100mg / dl). Among the risk factors 41% were overweight and 38% obese, 80% and 76% showed increased risk by measurement of WC and waist/hip ratio (WHR) respectively. A significant correlation between cholesterol and age (p = 0.004), cholesterol and CRP (p = 0.049), triglycerides and risk of CHD (p = 0.001) and triglycerides and waist/hip ratio (p = 0.006). The data from this study showed the importance of evaluating serum cholesterol levels in women as cardiovascular predictor of events and inflammatory processes in addition to the anthropometric parameters as predictor of serum triglycerides.